2022
DOI: 10.1111/jdv.18198
|View full text |Cite
|
Sign up to set email alerts
|

UV filters and their impact on marine life: state of the science, data gaps, and next steps

P. Lebaron

Abstract: Sunscreens containing broad‐spectrum ultraviolet (UV) filters play an essential role in protecting the skin against the damage induced by sun overexposure. However, the widespread use of sunscreens and other personal care products containing these filters has led to these compounds being widely detected in the environment and being identified as emerging pollutants in marine waters. Concerns raised by laboratory studies investigating the potential impact of UV filters on coral communities have already led to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
(159 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, in our efforts to promote photoprotection, we must equally consider the environmental consequences: UV filters, especially homosalate and benzophenones, have been found to be seriously harmful to marine life. 10 There is a need for research towards better, more environmentally friendly sunscreens. In advocating for climate change, JEADV has joined other major international dermatology journals in urging academic organizations to move beyond research and education, as well as in their day-to-day operations, including reduction in the carbon footprint of events such as conferences and congresses.…”
Section: Oncology a N D Ca Nce R Pr Ev E N Tionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in our efforts to promote photoprotection, we must equally consider the environmental consequences: UV filters, especially homosalate and benzophenones, have been found to be seriously harmful to marine life. 10 There is a need for research towards better, more environmentally friendly sunscreens. In advocating for climate change, JEADV has joined other major international dermatology journals in urging academic organizations to move beyond research and education, as well as in their day-to-day operations, including reduction in the carbon footprint of events such as conferences and congresses.…”
Section: Oncology a N D Ca Nce R Pr Ev E N Tionmentioning
confidence: 99%
“…Nevertheless, in our efforts to promote photoprotection, we must equally consider the environmental consequences: UV filters, especially homosalate and benzophenones, have been found to be seriously harmful to marine life 10 . There is a need for research towards better, more environmentally friendly sunscreens.…”
Section: Oncology and Cancer Preventionmentioning
confidence: 99%
“…1 In addition to these, environmental scientists have labelled certain ultraviolet radiation (UV) filter ingredients as 'contaminants of emerging concern' due to their potential to damage coral reefs. 2,3 This has sparked media-driven public attention and raised questions in minds of consumers regarding the overall safety profile of sunscreens, despite the clearly known health benefits of sunscreen use in reducing the incidence of squamous cell carcinoma and melanoma by 40% and 50%, respectively. 3 Ultraviolet filters can reach aquatic environments via direct wash-off from swimmers or indirectly from incomplete wastewater treatment.…”
Section: Reef Safe Sunscreens: a Call To Actionmentioning
confidence: 99%
“…8 Studies have demonstrated that nanoparticles of inorganic UV filters like titanium dioxide and zinc oxide can also have toxic effects on marine microalgae and zooplankton. 2,5 Only 15 of the 60 permitted UV filters worldwide have been tested for toxic effects on the marine environment, and thus, there is limited safety evidence for several UV filters. Thus, at present 'reef safe' labelling should be interpreted with caution since it has not been validated and is not scientifically justified.…”
Section: Reef Safe Sunscreens: a Call To Actionmentioning
confidence: 99%
See 1 more Smart Citation